The transplant patient biological, psychiatric, and ethical issues in organ transplantation - Trzepacz, Paula T.; DiMartini, Andrea F. (Cambridge University Press, 2000)
Organ transplantation is an essential element of treatment for a wide range of diseases, but despite increasing surgical success rates there remain many other issues affecting selection of patients and clinical outcome with which clinicians and patients themselves must be familiar. Originally published in 2000, this book reviews psychosocial, psychiatric and ethical aspects of organ transplantation in a uniquely authoritative way. Drawing heavily on the pioneering work of the Pittsburgh transplant team, it surveys the essentials of transplantation biology before engaging with a range of topics fundamental to the success of the procedure and the quality of life of recipients and donors alike. The interdisciplinary approach and the authority of the contributors will make this book of value to anyone with an interest in organ transplantation procedures
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Ethik; Psychologie; Transplantation of organs, tissues, etc / Physiological aspects; Transplantation of organs, tissues, etc / Psychological aspects; Transplantation of organs, tissues, etc / Moral and ethical aspects; Transplantation; Psychosoziale Belastung; Aufsatzsammlung